Type I interferon signalling in the intestinal epithelium affects Paneth cells, microbial ecology and epithelial regeneration. Issue 12 (20th February 2014) - Tschurtschenthaler, Markus; Wang, Jun; Fricke, Cornelia; Fritz, Teresa M J; Niederreiter, Lukas; Adolph, Timon E; Sarcevic, Edina; Künzel, Sven; Offner, Felix A; Kalinke, Ulrich; Baines, John F; Tilg, Herbert; et al.
Abstract : Objective: Intestinal epithelial cells (IECs) at the internal/external interface orchestrate the mucosal immune response. Paneth cells secrete antimicrobial peptides and inflammatory mediators, protect from pathogens and shape the commensal microbiota. Prompted by the genetic association of the locus harbouring the type I interferon (IFN) receptor ( IFNAR1 ) with Crohn's disease, and a transcriptional signature for type I IFN signalling in Paneth cells, we studied the function of IFNAR1 in IECs. Design: Type I IFN signalling was studied in mice with conditional deletion of Ifnar1 in IECs. Phenotype was characterised at baseline, and gut microbiota composition was assessed by 16S rDNA ribotyping. The role of IFNAR1 was also investigated in experimental colitis induced by dextran sodium sulfate (DSS) and colitis-associated cancer induced by DSS in conjunction with azoxymethane (AOM). Results: Ifnar1 −/−(IEC) mice displayed expansion of Paneth cell numbers and epithelial hyperproliferation compared with Ifnar1 -sufficient littermates. While Ifnar1 −/−(IEC) mice did not exhibit spontaneous inflammation or increased severity in DSS colitis compared with Ifnar1 +/+(IEC) mice, they exhibited an increased tumour burden in the AOM/DSS model. Both hyperproliferation and tumour promotion were dependent on the microbial flora, as the differences between genotypes were marked upon separately housing mice, but disappeared when Ifnar1 −/−(IEC) and Ifnar1 +/+(IEC) mice were co-housed. Accordingly, ribotyping revealed marked differences between Ifnar1 −/−(IEC) and Ifnar1 +/+(IEC) mice that where diminished upon co-housing. Conclusions: IFNAR1 in IECs, and Paneth cells in particular, contributes to the regulation of the host–microbiota relationship, with consequences for intestinal regeneration and colitis-associated tumour formation.